Developing multimodal communicative competence in emerging academic and professional genres - Ruiz-Madrid, Noelia; Valeiras-Jurado , Julia (International Journal of English Studies, 2020)
In this paper, we propose a pedagogical approach for teaching and learning multimodal literacy, specifically, the application of multimodal discourse analysis for genre awareness. The mastery of specific oral genres is seen as desirable to help students become competent professionals. This is the case of Product Pitches (PPs) in the business field and Research Pitches (RPs) in the academic field. The former are short presentations that introduce a product to the market, the latter constitute an emerging way of disseminating ongoing research to the general public. A salient characteristic of both is their multimodal nature, which has raised an increasing interest in multimodal approaches to genre pedagogy. Our aim is to develop students’ analytical skills to make them aware of the variety of semiotic modes and the importance of using them coherently. The pedagogical approach is facilitated by specialised software that supports the systematic teaching and learning of multimodal genres.